Hand Rub Consumption Has Almost Doubled in 132 German Hospitals Over 9 Years. (31st May 2017) - Wetzker, Wibke; Walter, Janine; Bunte-Schönberger, Karin; Schwab, Frank; Behnke, Michael; Gastmeier, Petra; Reichardt, Christiane
Abstract : Annual surveillance data (2007–2015), collected continuously in 132 German hospitals, was evaluated for development of alcohol-based hand-rub consumption (AHC) as a surrogate parameter for hand hygiene adherence. Overall, the median increase in AHC was 94%. The increases over 9 years were significant in all units and quartiles of AHC at baseline. Infect Control Hosp Epidemiol 2017;38:870–872